Pemikiran Pendidikan Islam K.H Ahmad Dahlan dan Implementasi dalam Sistem Pendidikan Ajaran Islam di Indonesia - Fika Fahria Rahmah (Research Institute and Community Engagement of UIN MADURA, 2026)
Islamic education in Indonesia faces modern challenges in the form of digitalization of education, character building, and religious moderation. In this context, the educational thought of K.H. Ahmad Dahlan is important to re-examine because it offers an integrative concept of tajdid (renewal) in Islamic education. However, previous research has focused more on the biography and history of Ahmad Dahlan's struggle than on the relevance of his thought to contemporary education. This study aims to analyze K.H. Ahmad Dahlan's concept of Islamic education and its implementation and relevance in the Islamic education system in Indonesia. The study uses a qualitative approach with library research methods through a historical-factual approach. Data were obtained from various primary and secondary sources in the form of journals and documents related to Ahmad Dahlan's thoughts, then analyzed using content analysis. The results show that Ahmad Dahlan's educational concept emphasizes the integration of religious knowledge with general knowledge, character building, intellectual development, and social awareness through the values ​​of Al-Ma'un. This tajdid concept is relevant to modern pedagogy, especially in strengthening character education, contextual learning, critical thinking, and religious moderation in the digital era. Thus, K.H Ahmad Dahlan's educational thoughts remain relevant as a basis for developing modern, adaptive and humanistic Islamic education..